Preparation method and application of Cu-based loaded Mo-N-C electrode
By supporting the Mo-N-C composite material on the Cu-based catalyst, the Cu-based supported Mo-N-C electrode is formed, which solves the problems of poor stability and low product selectivity in the electroreduction of carbon dioxide, and achieves the efficient and stable effect of converting CO2 into methanol.
Patent Information
- Application Number
- CN202510003632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-14
AI Technical Summary
The existing Cu-based catalysts have problems of poor stability and low product selectivity during the electroreduction of carbon dioxide, making it difficult to effectively catalyze the conversion of carbon dioxide into methanol.
The Cu-based supported Mo-N-C electrode is used to support the Mo-N-C composite material on the surface of the Cu-based catalyst, and the Mo/C composite material is used as the active site to promote the adsorption and activation of carbon dioxide, and the stability and product selectivity of the catalyst are improved through synergistic effects with the Cu-based catalyst.
It significantly improves the stability of the catalyst and CO2 conversion rate, extends the service life of the electrode, and maintains good activity and efficient methanol generation ability during the electrolysis process.
Smart Images

Figure HDA0005226215500000011 
Figure HDA0005226215500000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, and in particular to a preparation method of a Cu-based loaded Mo-NC electrode for catalyzing the electroreduction of carbon dioxide (CO2) to methanol and its application. Background Art
[0002] As global climate change and energy crisis become increasingly serious, the reduction and reuse of carbon dioxide has become a hot topic of research. Among them, carbon dioxide electroreduction technology has attracted much attention because it can convert carbon dioxide into valuable chemicals. However, the catalyst efficiency and stability of this technology are still facing great challenges, so the development of new and efficient catalysts is the key to this technology.
[0003] Methanol is not only an important chemical raw material, but also an excellent energy source and automotive fuel. Methanol is in a connecting position in the entire industrial chain. In industry, methanol is almost always synthesized by pressurized catalytic hydrogenation of carbon monoxide and carbon dioxide. The reduction of carbon dioxide to methanol through electrochemical reaction has the characteristics of green environmental protection and high purity. Therefore, the preparation of methanol by carbon dioxide reduction is a hot topic in current research. Cu-based catalysts have broad application prospects in the field of carbon dioxide electroreduction due to their unique electronic structure and catalytic performance. However, pure Cu catalysts have problems such as poor stability and low product selectivity in the catalytic process. Therefore, how to modify Cu-based catalysts and improve their catalytic performance and stability is an urgent problem to be solved in the industry. Summary of the invention
[0004] The present invention provides a method for preparing a Cu-based Mo-NC electrode and its application in the CO2 electrocatalytic generation of methanol reaction. The Cu-based Mo-NC electrode provided by the present invention comprises a substrate Cu and a Mo-NC composite material loaded on the surface of a Cu-based catalyst. The Mo / C composite material can serve as an active site to promote the adsorption and activation of carbon dioxide, and at the same time, through the synergistic effect with the Cu-based catalyst, improve the stability and product selectivity of the catalyst. Therefore, the catalyst has a stable structure during the CO2 electrolysis process, has a high CO2 electrolysis activity and a long service life.
[0005] The first object of the present invention is to provide a method for preparing a Cu-based Mo-NC electrode, comprising the following steps:
[0006] (1) preparing a catalyst slurry: adding a metal molybdenum salt and carbon powder to a dispersed emulsion and stirring uniformly to obtain a slurry A, adding a nitrogen source to the slurry A and stirring uniformly to obtain a catalyst precursor slurry B, and adding a binder to the slurry B and stirring uniformly to obtain a catalyst slurry;
[0007] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried to obtain an electrode precursor;
[0008] (3) Pressing: Pressing the electrode precursor and the hydrophobic membrane into shape;
[0009] (4) Calcination: The electrode prepared in step (3) is calcined under a protective atmosphere to prepare a Mo-NC electrode.
[0010] Furthermore, the metal molybdenum salt in step (1) is one or more of molybdenum acetate, molybdenum nitrate, molybdenum sulfate, and molybdenum chloride;
[0011] The dispersed emulsion is selected from EVA resin sol, carbomer emulsion, methyl cellulose, carboxyethyl cellulose, ethyl cellulose, carboxymethyl cellulose solution or starch solution, preferably EVA resin sol; the mass ratio of the metal salt to the dispersed emulsion is 1:5 to 1:10; the preferred mass ratio of the metal salt to the dispersed emulsion is 1:5 to 1:8;
[0012] Furthermore, in step (1), the mass ratio of the carbon powder to the dispersed emulsion is 1:20 to 1:50; preferably, the mass ratio of the carbon powder to the dispersed emulsion is 1:30 to 1:40;
[0013] Furthermore, the nitrogen source is selected from dicyandiamide, urea, cyanamide, amino acids, nitrates, and ammonium salts, preferably dicyandiamide.
[0014] Furthermore, in step (1), the mass ratio of the nitrogen source to the dispersed emulsion is 1:10 to 1:15; preferably, the mass ratio of the nitrogen source to the dispersed emulsion is 1:12 to 1:15;
[0015] Furthermore, the binder is styrene-butadiene rubber emulsion, polyacrylic acid emulsion, polyvinyl alcohol emulsion, PVDF or Nafion solution.
[0016] Furthermore, in step (1), the mass ratio of the binder to the dispersed emulsion is 1:8 to 1:15; preferably, the mass ratio of the binder to the dispersed emulsion is 1:10 to 1:12.
[0017] Furthermore, in step (2), the catalyst slurry loading is 10-600 mg / cm 2 ; preferably 100-500mg / cm 2 .
[0018] Furthermore, in step (2), the drying temperature is 20-80°C for 1-6 hours; preferably, the drying temperature is 20-80°C and the drying time is 1-6 hours;
[0019] Furthermore, in step (3), the pressure applied during the pressing process is 1-20 kPa; preferably, the pressure applied during the pressing process is 10-15 kPa.
[0020] Furthermore, in step (3), the hydrophobic membrane is a polytetrafluoroethylene membrane.
[0021] Furthermore, in step (4), the protective atmosphere is one or more of nitrogen, inert gas or air;
[0022] Furthermore, in step (4), the temperature is raised to 100-260° C. and calcined for 1-40 h at a heating rate of 10-20° C. / min; the preferred calcination time is 12-24 h;
[0023] The present invention also provides the use of the Cu-based loaded Mo-NC electrode in the CO2 electrolytic reduction reaction to prepare methanol.
[0024] A method for preparing methanol by electrolytic reduction of CO2, using the electrode prepared by the preparation method of the present invention as a cathode.
[0025] Preferably, the cathode electrolyte is a KOH or KHCO3 solution; preferably a KOH or KHCO3 solution with a concentration of 0.1-2 mol / L, more preferably a KOH or KHCO3 solution with a concentration of 0.5-1 mol / L;
[0026] Preferably, the anode for the CO2 electrolytic reduction reaction to produce methanol is an iridium tandem electrode;
[0027] Preferably, the anolyte for the CO2 electrolytic reduction reaction to produce methanol is a H2SO4 solution; preferably a H2SO4 solution with a concentration of 0.1-1 mol / L, more preferably a H2SO4 solution with a concentration of 0.2-0.5 mol / L;
[0028] Preferably, the membrane for the CO2 electrolytic reduction reaction to produce methanol comprises a proton exchange membrane;
[0029] Preferably, CO2 is introduced into the cathode electrolyte for electrolysis reaction, and the CO2 gas flow rate is 10-50 ml / min, preferably 20-30 ml / min;
[0030] The current density applied in the CO2 electrolytic reduction reaction to prepare methanol is 500-5000A / m 2 The preferred applied current density is 1000-2000A / m 2 and / or,
[0031] The electrolysis time of the CO2 electrolytic reduction reaction to prepare methanol is 1-3 hours.
[0032] Compared with the prior art, the beneficial effects of the technology of the present invention are:
[0033] (1) The present invention synthesizes Mo-NC catalyst slurry, and the Mo catalyst is calcined and carbonized on a Cu conductive substrate to form an integrated catalytic electrode, thereby improving the adhesion between the catalyst layer and the hydrophobic layer and the conductive substrate, thereby significantly enhancing the stability of the catalyst layer;
[0034] (2) The present invention uses calcination to sinter the electrode, which mainly plays a role in pore formation, so that the Mo-NC catalyst is evenly dispersed on the electrode surface, increasing the catalyst reaction active sites; nitrogen-containing compounds are added to the catalyst slurry, and nitrogen sites are introduced after carbonization to form a metal-nitrogen-carbon catalyst layer, which increases the adsorption capacity of CO2, thereby improving the CO2 conversion rate;
[0035] (3) The CO2 electroreduction to methanol electrode prepared by the present invention has a larger specific surface area, higher catalyst stability and longer service life, and exhibits good activity and CO2 conversion rate during the electrolysis process. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the appearance of the Cu-based supported Mo-NC catalyst of the present invention;
[0037] Figure 2 This is a performance curve diagram of the Cu-based supported Mo / C catalyst in Example 1 of the present invention in the electrocatalytic carbon dioxide reduction reaction. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0039] Source of raw materials:
[0040] Nafion solution, PTFE emulsion (polytetrafluoroethylene emulsion): Inokane reagent
[0041] Dicyandiamide: Inokane reagent
[0042] Embodiment 1:
[0043] (1) adding 1 g of platinum nitrate and 0.25 g of carbon powder to 10 g of carbomer emulsion and stirring evenly to obtain slurry A, adding 1 g of dicyandiamide to slurry A and stirring evenly to obtain catalyst precursor slurry B, and adding 1 g of PTFE emulsion to slurry B and stirring evenly to obtain catalyst slurry;
[0044] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried at 35°C to obtain an electrode precursor;
[0045] (3) Pressing: Pressing the electrode precursor and the PTFE hydrophobic membrane into shape;
[0046] (4) Calcination: The electrode (3) was calcined in an air atmosphere at a heating rate of 15° C. / min to 260° C. for 24 h to prepare a Mo-NC electrode.
[0047] The electrode prepared in this example was used as a cathode material for CO2 electroreduction. The cathode liquid was 1 mol / L KOH solution, the anode was an iridium-tantalum electrode, the anode liquid was 0.5 mol / L H2SO4 solution, the CO2 gas flow rate was 30 ml / min, and the pressure was 2000 A / m 2 At the current density, the methanol current efficiency reaches 85%.
[0048] Embodiment 2:
[0049] (1) dissolving 1 g of molybdenum chloride and 0.21 g of carbon powder in 10 g of carbomer emulsion and stirring to obtain slurry A, dissolving 0.8 g of dicyandiamide in slurry A and stirring to obtain catalyst precursor slurry B, and dissolving 1 g of PTFE emulsion in slurry B and stirring to obtain catalyst slurry;
[0050] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried at 35°C to obtain an electrode precursor;
[0051] (3) Pressing: Pressing the electrode precursor and the PTFE hydrophobic membrane into shape;
[0052] (4) Calcination: The electrode (3) is calcined in an air atmosphere at a temperature increase rate of 20° C. / min, and the temperature is raised to 180° C. and calcined for 24 h to prepare a Mo-NC electrode.
[0053] The electrode prepared in this example was used as a cathode material for CO2 electroreduction. The cathode liquid was 1 mol / L KOH solution, the anode was an iridium-tantalum electrode, the anode liquid was 0.5 mol / L H2SO4 solution, the CO2 gas flow rate was 30 ml / min, and the pressure was 2000 A / m 2 At the current density, the methanol current efficiency reaches 84%.
[0054] Embodiment 3:
[0055] (1) dissolving 1 g of molybdenum chloride and 0.15 g of carbon powder in 5 g of carbomer emulsion and stirring to obtain slurry A, dissolving 0.5 g of urea in slurry A and stirring to obtain catalyst precursor slurry B, and dissolving 0.5 g of PTFE emulsion in slurry B and stirring to obtain catalyst slurry;
[0056] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried at 35°C to obtain an electrode precursor;
[0057] (3) Pressing: Pressing the electrode precursor and the PTFE hydrophobic membrane into shape;
[0058] (4) Calcination: The electrode (3) is calcined in an air atmosphere at a heating rate of 10° C. / min to 220° C. and calcined for 24 h to prepare a Mo-NC electrode.
[0059] The electrode prepared in this example was used as a cathode material for CO2 electroreduction. The cathode liquid was 1 mol / L KOH solution, the anode was an iridium-tantalum electrode, the anode liquid was 0.5 mol / L H2SO4 solution, the CO2 gas flow rate was 30 ml / min, and the pressure was 2000 A / m 2 At the current density, the methanol current efficiency reaches 80%.
[0060] Embodiment 4:
[0061] (1) 1.5 g of platinum nitrate and 0.35 g of carbon powder were dissolved in 10 g of EVA resin sol and stirred to obtain slurry A, 1 g of dicyandiamide was dissolved in slurry A and stirred to obtain catalyst precursor slurry B, and 0.8 g of PTFE emulsion was dissolved in slurry B and stirred to obtain catalyst slurry;
[0062] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried at 45°C to obtain an electrode precursor;
[0063] (3) Pressing: Pressing the electrode precursor and the PTFE hydrophobic membrane into shape;
[0064] (4) Calcination: The electrode prepared in (3) was calcined in a nitrogen atmosphere at a heating rate of 15° C. / min to 240° C. for 24 h to prepare a Mo-NC electrode.
[0065] The electrode prepared in this example was used as a cathode material for CO2 electroreduction. The cathode liquid was a 0.5 mol / L KOH solution. The anode was an iridium-tantalum electrode. The anode liquid was a 0.3 mol / L H2SO4 solution. The CO2 gas flow rate was 30 ml / min. At 2000 A / m 2 At the current density, the methanol current efficiency reaches 87%.
[0066] Embodiment 5:
[0067] (1) dissolving 1 g of molybdenum nitrate and 0.25 g of carbon powder in 10 g of carbomer emulsion and stirring to obtain slurry A, dissolving 1 g of ammonium nitrate in slurry A and stirring to obtain catalyst precursor slurry B, and dissolving 1.2 g of PTFE emulsion in slurry B and stirring to obtain catalyst slurry;
[0068] (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried at 35°C to obtain an electrode precursor;
[0069] (3) Pressing: Pressing the electrode precursor and the PTFE hydrophobic membrane into shape;
[0070] (4) Calcination: The electrode prepared in (3) was calcined in an air atmosphere at a heating rate of 15° C. / min to 240° C. for 24 h to prepare a Mo-NC electrode.
[0071] The electrode prepared in this example was used as a cathode material for CO2 electroreduction. The cathode liquid was 1 mol / L KOH solution, the anode was an iridium-tantalum electrode, the anode liquid was 0.8 mol / L H2SO4 solution, the CO2 gas flow rate was 25 ml / min, and the pressure was 1000 A / m 2 At the current density, the methanol current efficiency reaches 81%.
[0072] Comparative Example 1
[0073] The reaction of preparing methanol by electrolytic reduction of CO2 was carried out in the same manner as in Example 1, the main difference being that no nitrogen source was added during the preparation of the cathode electrode, and the methanol current efficiency was 55%.
Claims
1. A method for preparing a Cu-based Mo-NC electrode, characterized in that: The steps include: (1) preparing a catalyst slurry: adding a metal molybdenum salt and carbon powder to a dispersed emulsion and stirring uniformly to obtain a slurry A, adding a nitrogen source to the slurry A and stirring uniformly to obtain a catalyst precursor slurry B, and adding a binder to the slurry B and stirring uniformly to obtain a catalyst slurry; (2) Loading: The obtained catalyst slurry is coated on a Cu mesh and dried to obtain an electrode precursor; (3) Pressing: Pressing the electrode precursor and the hydrophobic membrane into shape; (4) Calcination: The electrode prepared in step (3) is calcined under a protective atmosphere to prepare a Mo-NC electrode.
2. The preparation method according to claim 1, characterized in that: The metal molybdenum salt in step (1) is one or more of molybdenum acetate, molybdenum nitrate, molybdenum sulfate and molybdenum chloride; Further, the dispersed emulsion is selected from EVA resin sol, carbomer emulsion, methyl cellulose, carboxyethyl cellulose, ethyl cellulose, carboxymethyl cellulose solution or starch solution, preferably EVA resin sol; The mass ratio of the metal salt to the dispersed emulsion is 1:5 to 1:10; the preferred mass ratio of the metal salt to the dispersed emulsion is 1:5 to 1:8; Furthermore, in step (1), the mass ratio of the carbon powder to the dispersed emulsion is 1:20 to 1:50; preferably, the mass ratio of the carbon powder to the dispersed emulsion is 1:30 to 1:
40.
3. The preparation method according to claim 1 or 2, characterized in that: The nitrogen source is selected from dicyandiamide, urea, cyanamide, amino acids, nitrates, and ammonium salts, preferably dicyandiamide; Furthermore, in step (1), the mass ratio of the nitrogen source to the dispersed emulsion is 1:10 to 1:15; preferably, the mass ratio of the nitrogen source to the dispersed emulsion is 1:12 to 1:15; Furthermore, the binder is styrene-butadiene rubber emulsion, polyacrylic acid emulsion, polyvinyl alcohol emulsion, PVDF or Nafion solution; Furthermore, in step (1), the mass ratio of the binder to the dispersed emulsion is 1:8 to 1:15; Furthermore, the mass ratio of the binder to the dispersed emulsion is 1:10 to 1:
12.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2), the loading amount of the catalyst slurry is 10-600 mg / cm 2 ; preferably 100-500mg / cm 2 . In step (2), the drying temperature is 20-80° C. for 1-6 hours; Further, the drying temperature is 20-80°C and the drying time is 1-6h; Furthermore, in step (3), the pressure applied during the pressing process is 1-20 kPa; preferably, the pressure applied during the pressing process is 10-15 kPa; Furthermore, in step (3), the hydrophobic membrane is a polytetrafluoroethylene membrane.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (4), the protective atmosphere is one or more of nitrogen, inert gas or air; Furthermore, in step (4), the temperature is raised to 100-260° C. and calcined for 1-40 h at a heating rate of 10-20° C. / min; the preferred calcination time is 12-24 h.
6. Use of a Cu-based Mo-NC electrode prepared by the preparation method according to any one of claims 1 to 5 in the reaction of producing methanol by CO2 electrolysis reduction.
7. A method for preparing methanol by electrolytic reduction of CO2, using the electrode prepared by the preparation method according to any one of claims 1 to 5 as a cathode.
8. The method according to claim 7, characterized in that The cathode electrolyte is a KOH or KHCO3 solution; preferably a KOH or KHCO3 solution with a concentration of 0.1-2 mol / L, more preferably a KOH or KHCO3 solution with a concentration of 0.5-1 mol / L; Preferably, the anode for the CO2 electrolytic reduction reaction to produce methanol is an iridium tandem electrode; Preferably, the anolyte for the CO2 electrolytic reduction reaction to produce methanol is a H2SO4 solution; preferably a H2SO4 solution with a concentration of 0.1-1 mol / L, more preferably a H2SO4 solution with a concentration of 0.2-0.5 mol / L; Preferably, the membrane for the CO2 electrolytic reduction reaction to produce methanol comprises a proton exchange membrane; Preferably, CO2 is introduced into the cathode electrolyte for electrolysis reaction, and the CO2 gas flow rate is 10-50 ml / min, preferably 20-30 ml / min; Preferably, the current density applied in the CO2 electrolytic reduction reaction to produce methanol is 500-5000A / m 2 The preferred applied current density is 1000-2000A / m 2 ; Preferably, the electrolysis time of the CO2 electrolytic reduction reaction to produce methanol is 1-3 hours.